2023
DOI: 10.2147/dmso.s404788
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Electrolyte Imbalance and Associated Factors Among Adult Diabetic Patients Attending the University of Gondar Comprehensive Specialized Hospital, Ethiopia: A Comparative Cross-Sectional Study

Abstract: Introduction: Electrolyte imbalance refers to altered electrolyte levels that predominantly affect diabetic patients due to hyperglycemia which rise plasma osmolality and impaired renal function, contributing to a change in electrolyte level. Therefore, this study aimed to assess the prevalence of electrolyte imbalance and its associated factors among diabetic patients and healthy control groups attending the University of Gondar Comprehensive Specialized Hospital. Patients and Methods: A comparative cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Chloride is a crucial electrolyte in charge of controlling body fluids, delivering nerve impulses, and preserving acid-base balance in the body. It was reported that electrolyte imbalance results from excess chloride in the blood (Eshetu et al, 2023). Elevated chloride levels in water bodies risk species' survival, development, and reproduction by endangering the sustainability of ecological food supplies (Tolulope et al, 2019;Imo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chloride is a crucial electrolyte in charge of controlling body fluids, delivering nerve impulses, and preserving acid-base balance in the body. It was reported that electrolyte imbalance results from excess chloride in the blood (Eshetu et al, 2023). Elevated chloride levels in water bodies risk species' survival, development, and reproduction by endangering the sustainability of ecological food supplies (Tolulope et al, 2019;Imo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%